Management practices in the beel aquaculture system at Rajshahi, northwest Bangladesh - Akter, S; Ali, MR; Mondol, MMR (Journal of Bio-Science, 2019)
Open aquatic system such as beel is an important freshwater resource for agriculture and aquaculture.This study was conducted (July-December 2014) to describe the beel aquaculture management practices in the Hagla Beel at Bagmara upazila under Rajshahi district.The Beel fish farming area was 20.25 ha and irregular in shape with average depth 1.5 m. During the study period, the measured water quality parameters of the beel were within the suitable range for aquaculture. Eight genera of phytoplankton and eight genera of zooplankton were identified from the beel water body. Four native and 4 exotic fish species with sizes ranging from 0.15-1.11 kg were stocked for growing in the beel. At the end of culture period, the production of fish was 2,622.15 kg/ha and cost-benefit ratio (CBR) was 1:1.42. Environmental problems such as increasing of water temperature and decreasing of water level during summer, and parasitic diseases were some of the risks in beel fish farming system. The results of this study should be useful for beel aquaculture, and for the farmers and resource manager for harnessing maximum benefits from the beel resources in Bangladesh. J. bio-sci. 28: 43-50, 2020